THE QUALITY OF TEACHER-MADE TEST IN EFL CLASSROOM AT THE ELEMENTARY SCHOOL AND ITS WASHBACK IN THE LEARNING - Desrin Lebagi; S. Sumardi; S. Sudjoko (Journal of English Education, 2017)
One of essential phases in language learning is measurement. Test as a tool of measurement process must then be well constructed. The quality of test itself can be determined through test item analysis. However, in some occasions, teachers tend to ignore test item analysis because of time limitation and other responsibilities.  Referring to this problem, this research aimed to describe the quality of test items including the difficulty index, the discrimination index, the distractor index, and the reliability of the test and the Washback of teacher-made test on students’ motivation in learning English. It was conducted at Gamaliel Elementary School in academic year of 2016-2017. This case study utilized purposive sampling. In collecting the data, the researcher used interview, observation, and document analysis as the techniques of collecting data. The informants were an English teacher and students of Gamaliel Elementary School. The documents were students’ answer sheets. In analyzing test items, the researchers used ITEMAN program. The result of this study shows that the teacher-made test can be classified in good test. The test brings both positive and negative Washback in students’ motivation in learning. Therefore, it is recommended for the teacher to conduct test analysis as a way of evaluating and improving his teaching and learning and test itself as well as to encourage the students to study even though they are not confronted with a test.